IMPLEMENTASI KEBIJAKAN PROGRAM JAMINAN KESEHATAN MASYARAKAT DI PUSKESMAS NIPA KECAMATAN NUSA TABUKAN KABUPATEN KEPULAUAN SANGIHE - HARTATI, DWI PUJI; KIYAI, BURHANUDDIN; LALOMA, ALDEN (Sam Ratulangi University, 2014)
Center Nusa Nipa Tabukan and what are the factors that hinder the implementationprocesspolicy.for answer the problem in this study , the data collection was conducted through interviewswith 13 informants consisting of : 1 person holder of a health program in PHC Nipa , health center employeesNipa 4 , 5 community health card holders , 3 poor people are not holding a health card . In general , almostall indicators of a health policy implementation programs organized by relevant agencies has been goodenough . Referring to the findings in this study , it is necessary to give some suggestions , as follows : PolicyJAMKESNAS program should be This study aims to determine how the implementation of a health programin the District Health implemented to the fullest to the public especially disadvantaged communitiesspecifically , so that people can feel satisfaction in the good and excellent service from the staff and can feelthe benefits of a health program and health services provided puskesmas.thenofficers should be enhanced because it is still found some weaknesses , especially in terms of providing healthcard to the people who have not been targeted and more in priority vehicle for patient referrals . Improvingthe health card services with emphasis on professionalism , transparency , effectiveness , efficiency , andresponsiilitas .Keywords : Policy Implementation in the public health insurance program homeland sub-district healthcenters tabukan nipa district Sangihe archipelagoâ€.